Upaya Sekolah Dalam Meminimalisir Keterlambatan Masuk Kelas Siswi Kelas VIII Di MTS Al-Mardliyyah - Jannah, Faridatul; B, Nurhasin; Wahyudi, Ahmad (STAI Publisistik Thawalib Jakarta, 2022)
The purpose of this research is to find out what factors influence student tardiness and what efforts are made by schools to minimize student tardiness. type of descriptive qualitative research. Data collection methods are observation, interviews, and documentation. Data analysis methods are data reduction, data display, and conclusion drawing/verification. The results of the study: the delay in entering class was caused by two factors: first, internal factors such as the desire of students to carry out disciplinary behavior. Both external factors, such as environmental influences, friends and student activities outside school time. Efforts made to minimize delays are: coaching the homeroom teacher, handling cases of mild to severe violations by counseling teachers and the student body at school.